2020
DOI: 10.1186/s40798-020-00246-x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised, Placebo-Controlled, Crossover Study Investigating the Optimal Timing of a Caffeine-Containing Supplement for Exercise Performance

Abstract: Background Pre-exercise supplements containing low doses of caffeine improve endurance exercise performance, but the most efficacious time for consumption before intense endurance exercise remains unclear, as does the contribution of caffeine metabolism. Methods This study assessed the timing of a commercially available supplement containing 200 mg of caffeine, 1600 mg of β-alanine and 1000 mg of quercetin [Beachbody Performance Energize, Beachbody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
9
0
1
Order By: Relevance
“…These data are in agreement with the results from other intermittent sports such as tennis in which caffeine ingestion improved the number of successful shots during a serve tennis performance test with minimal influence of the CYP1A2 genotype [36]. These combined results, in terms of genotype, reinforce the idea that the CYP1A2 genotype has little influence on the ergogenic response to caffeine, as previously found in other forms of exercise [11,23,24,[32][33][34][35][36]. Thus, despite findings associated with a higher ergogenic response to caffeine in CYP1A2 AA athletes with respect to C-allele athletes [22,29], the current investigation suggests that the ergogenic effect of caffeine on neuromuscular performance may be independent of the −163 C > A CYP1A2 genotype, at least in handball players.…”
Section: Cyp1a2supporting
confidence: 90%
See 1 more Smart Citation
“…These data are in agreement with the results from other intermittent sports such as tennis in which caffeine ingestion improved the number of successful shots during a serve tennis performance test with minimal influence of the CYP1A2 genotype [36]. These combined results, in terms of genotype, reinforce the idea that the CYP1A2 genotype has little influence on the ergogenic response to caffeine, as previously found in other forms of exercise [11,23,24,[32][33][34][35][36]. Thus, despite findings associated with a higher ergogenic response to caffeine in CYP1A2 AA athletes with respect to C-allele athletes [22,29], the current investigation suggests that the ergogenic effect of caffeine on neuromuscular performance may be independent of the −163 C > A CYP1A2 genotype, at least in handball players.…”
Section: Cyp1a2supporting
confidence: 90%
“…However, to date, findings have been controversial, with some studies reporting a higher response to caffeine in AA athletes [22,29] and other studies showing a better response to caffeine in C-carrier athletes [30]. Overall, most of the investigations have found that the ergogenic response to caffeine is independent of the CYP1A2 −163 C > A polymorphism [11,23,24,[31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…One study report on caffeine consumption derived from energy drinks in cyclists, presented by Davenport et al [111]. They found that a 200 mg supplement of caffeine 35 min before exercise seemed optimal to improve performance in a time trial, reducing the perception of effort in which the individuals with genotype AA of CYP1A2.…”
Section: Energy Drinks Sport Performance and Geneticsmentioning
confidence: 99%
“…Several studies explored the effects of caffeine supplementation on exercise performance while considering CYP1A2 −163C>A polymorphism [9][10][11][12][13]. The results of these studies, however, are equivocal.…”
Section: Introductionmentioning
confidence: 99%